HUBUNGAN KADAR GLIAL FIBRILLARY ACIDIC PROTEIN GFAP SERUM DENGAN LUARAN KLINIS NEUROLOGIS PASIEN STROKE HEMORAGIK - Theodorus Kevin Hendartono,* Retnaningsih,* Amin Husni* (Neurona Majalah Kedokteran Neuro Sains, 2018)
INTRODUCTION GLIAL FIBRILLARY ACIDIC PROTEIN GFAP IS A PROTEIN THAT IS RESPONSIBLE FOR THE CYTOSKELETON STRUCTURE OF GLIAL CELLS INCREASED LEVEL OF GFAP CAN BE USED TO PREDICT THE LEVEL OF GLIAL CELLS DAMAGE THAT ACCOMPANIES A HEMORRHAGIC STROKE NATIONAL INSTITUTE OF HEALTH STROKE SCALE NIHSS AND MODIFIED RANKIN SCALE MRS ARE THE MEASUREMENT SCALES THAT HAVE HIGH VALIDITY AND RELIABILITY FOR DETERMINING THE LONGTERM FUNCTIONAL CLINICAL OUTPUT OF HEMORRHAGIC STROKE PATIENTS